Neurological complications induced by immune checkpoint inhibitors: a comprehensive descriptive case-series unravelling high risk of long-term sequelae. Issue 4 (1st October 2021) - Plaçais, Léo; Michot, Jean-Marie; Champiat, Stéphane; Romano-Martin, Patricia; Baldini, Capucine; Joao, Maria Silva; Marabelle, Aurélien; Voisin, Anne-Laure; Not, Adeline; Labeyrie, Céline; Beaudonnet, Guillemette; Laparra, Ariane; et al.
Abstract: Neurological immune-related adverse events are complications of programmed-cell death 1 or programmed-cell death 1 ligand immunotherapies that can be life threatening and often lead to anticancer immunotherapy withdrawal. Scant clinical data are available that integrate the clinical presentation, therapeutic management and long-term outcome. All consecutive adult patients treated by programmed-cell death 1 or programmed-cell death 1 ligand immunotherapies, given alone or in combination with other treatment, who experienced a neurological immune-related adverse event with a severity grade ≥2 in Paris Saclay-University hospitals were investigated from June 2014 to February 2019. The frequency of neurological immune-related adverse events was calculated from the prospective Registre des Effets Indésirables Sévères des Anticorps Monoclonaux Immunomodulateurs en Cancérologie cohort. Forty patients presenting with 51 distinct neurological immune-related adverse events were included. The prevalence of grade ≥2 neurological immune-related adverse events was estimated to be 1.22% in the Registre des Effets Indésirables Sévères des Anticorps Monoclonaux Immunomodulateurs en Cancérologie cohort. Among 40 patients with neurological immune-related adverse events, 65% received programmed-cell death 1 or programmed-cell death 1 ligand monotherapy and 35% received a combination of programmed-cell death 1 plus anti-CTLA4 (Common Terminology Criteria for Adverse Events). Clinical neurological presentations were peripheral (48%), central (35%), or mixed (18%). The severity of neurological immune-related adverse events was grade 2 for 14 (35%) and ≥grade 3 for 26 patients (65%). The mortality rate related to neurological immune-related adverse events was 8%. Corticosteroid treatment led to neurological recovery in 74%. Long-term follow-up highlighted that 53% of patients experienced long-term neurological sequelae. Five patients were rechallenged by programmed-cell death 1 monotherapy without recurrence of their neurological immune-related adverse event(s). Neurological immune-related adverse events induced by programmed-cell death 1 or programmed-cell death 1 ligand are rare but are severe with a mortality rate of 8% and long-term sequelae for 53% of patients. Corticosteroids should be started when neurological immunological complications are identified to avoid long-term sequelae. Abstract : Plaçais et al. report a large case-series of 40 patients presenting with 51 neurological adverse events of immune checkpoint inhibitors, wherein corticosteroid therapy was associated with a 74% rate of neurological recovery. Neurological adverse events were severe, as 7.5% of the included patients died and 53% kept long-term neurological sequelae. Graphical Abstract: